Child Educational Content on Digital Folklore "Pak Lebai Malang": A Qualitative Content Analysis - Faeruz, Ratna; Rahiem, Maila D.H.; Surayyah Madhubala Abdullah, Nur; Rahmat Romadhon, Dzikri; Sari Dewi, Ratna; Rahmatullah, Rahmatullah; Rosyada, Dede (Al-Athfal: Jurnal Pendidikan Anak, 2021)
Purpose – The purpose of this study was to explore child educational content digital folklore on YouTube, and It is used to teach young children about science, language, and values. The unit analysis on this research was the video of Pak Lebai Malang from West Sumatera, Indonesia.Design/methods/approach – The qualitative content analysis method was used in this study. The content analyzed was digital folklore based on the Minangkabau story Pak Lebai Malang. The process began with downloading the video, creating a transcript, taking notes on the text, language, and context, re-watching the video, comparing and contrasting it to the memo, and eliciting evidence from the video.Findings – The data revealed the following ways in which digital folklore on YouTube teaches science, language, and values: 1) digital technology illustrates science concepts with simple-to-understand videos; 2) by repeating the words and visualizing each spoken word, YouTube videos teach children new vocabulary. 3) the characters’ expressions and intonation in the video teach children about social values.Research implications/limitations – This research could serve as a springboard for future research on the use of digital folklores in early childhood classrooms. It is advised that additional research be conducted to improve the interest, effectiveness, and applicability of digital folklore in the early childhood learning process and design more effective programs for teaching science, language, and value to young people children. The study’s drawback is that it analyzes only one video. If it is compared to other videos, it may provide a complete view. Practical implications – This study informs educators on the potential for using digital folklore to teach science, language, and values. It entails the implementation of more creative strategies in early childhood education. Additionally, the study inspires innovative content creators on YouTube to make their videos more relevant to young children’s learning. Additionally, parents may discover that something as simple as a YouTube video could be an incredible resource for their child’s development.Originality/value – The study explains child educational content based on local wisdom. The digital form of Pak Lebai Malang folklore can facilitate accessibility and acceptability. Paper type Research paper